2018
DOI: 10.1111/jfpe.12871
|View full text |Cite
|
Sign up to set email alerts
|

Mild‐thermal and high pressure processing inactivation kinetics of polyphenol oxidase from peach puree

Abstract: This study has investigated the inactivation of polyphenoloxidase (PPO) in peach puree during thermal (50–60 °C, 2–30 min) and combined high pressure‐mild thermal treatment (HPMT) (200–600 MPa, 25–45 °C, and 2–23 min). HPMT resulted immediately after treatment in an increase in PPO activity up to 66.50% at 200 MPa and 45 °C compared with the untreated samples. The reaction order (nth) of PPO thermal inactivation was 1.951 (0.1 MPa, 50–60 °C) and 0.953 for the HPMT treatment (200–600 MPa, 25–45 °C). Fractional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 31 publications
0
8
1
2
Order By: Relevance
“…The current study found a more labile PPO compared to other studies performed in strawberry or peaches alone [8,25]. After two weeks of storage the activity of PPO in the TT sample was reactivated to a value two-fold higher than in the first day after the treatment.…”
Section: Phcontrasting
confidence: 50%
See 4 more Smart Citations
“…The current study found a more labile PPO compared to other studies performed in strawberry or peaches alone [8,25]. After two weeks of storage the activity of PPO in the TT sample was reactivated to a value two-fold higher than in the first day after the treatment.…”
Section: Phcontrasting
confidence: 50%
“…The PPO activity was determined according to the method described by [8]. Briefly, to determine PPO activity, 0.350 mL of extract was mixed in 1.420 mL McIlvaine buffer (pH 6.6) and 0.730 mL 0.175 M pyrocatechol was added.…”
Section: Ppo Activity Assaymentioning
confidence: 99%
See 3 more Smart Citations